Exploring the role of digital infrastructure in school accreditation across types and geographies - Supardi, Supardi; Agustina, Titik; Muslimin, Afif Ikhwanul (Edelweiss Applied Science and Technology, 2024)
This study examines the role of digital infrastructure in shaping school accreditation outcomes across public and private institutions in urban and suburban settings in Indonesia. Utilizing a quantitative correlational approach, data from 643 schools, including information on digital infrastructure, school types, geographical location, and accreditation scores, were analyzed. The results revealed a moderate positive correlation between digital infrastructure availability and accreditation outcomes, with public schools and urban schools generally outperforming their counterparts in suburban areas. Public schools benefited from superior access to digital tools, such as high-speed internet and smart classrooms, due to government funding, while private schools often faced resource limitations. Geographical disparities were also evident, with urban schools achieving higher digital readiness and better accreditation scores compared to suburban schools. These findings highlight systemic inequities in digital access that influence accreditation outcomes, emphasizing the need for targeted policies to bridge the digital divide. Interventions should prioritize under-resourced private schools and suburban areas to promote equitable educational opportunities and improve accreditation standards. This research contributes to the broader discourse on education equity and provides actionable insights for policymakers and educators aiming to enhance digital infrastructure in diverse educational contexts.